A Systematic Mixed Studies Review of the Intersections of Social–Ecological Factors and HIV Stigma in People Living With HIV in the U.S. South. (May 2019) - Ingram, LaDrea; Stafford, Crystal; Deming, Michelle E.; Anderson, Joi D.; Robillard, Alyssa; Li, Xiaoming
Abstract : Abstract: The role of stigma on psychological wellness and treatment outcomes in people living with HIV (PLWH) has been well documented. However, within the context of the southern United States, the intersection between HIV-related stigma and social–ecological factors has been understudied. Thus, a results-based convergent, mixed synthesis design was used to examine the manifestations of HIV-related stigma in PLWH in the U.S. South. A literature search was conducted using PsycINFO, PubMed (includes MEDLINE), and CINAHL. The first level of screening by title and abstract was administered on 1, 829 articles. A full-text screening of 169 studies was completed, and a total of 30 relevant articles were extracted. The mixed synthesis highlighted intervention strategies that can reduce HIV-related stigma while promoting positive health-behavior change. The findings of this review underscored the uniqueness of PLWH in the south and demonstrated the crucial role of intersectionality in investigating HIV-related stigma in treating and preventing HIV.